Writing as a Tool in Teaching Sketching: Implications for Architectural Design Education - Soygenis, Sema; Soygenis, Murat; Erktin, Emine (WILEY-BLACKWELL, 2010)
This article discusses the process of a study designed to develop university students' sketching skills in schools of architecture. Acknowledging the relationship between cognition and writing, it aims to investigate the role of writing in learning sketching among architecture students and to examine how students regulate their thoughts by writing as they work on their free hand sketches. It includes writing texts before and after sketching tasks to improve sketching. The study was implemented in a school of architecture at a Turkish university as part of an elective course on sketching. The students' works were evaluated in terms of their sketches, texts and self-reports of their thinking and the views and comments of the tutor who carried out the programme. This article discusses how the study was conceived and developed. The results of this study may provide insights for educators in developing strategies in teaching and learning of sketching and design, using multi modes of thinking.
Keywords: VISUAL THINKING; Art; Education & Educational Research